2021
DOI: 10.1016/j.ijid.2021.02.103
|View full text |Cite
|
Sign up to set email alerts
|

Tackling TB in migrants arriving at Europe’s southern border

Abstract: Over a quarter of the individuals diagnosed with tuberculosis [TB] in the European Union region are born outside of the area and the proportion has been increasing steadily. Italy is a low TB incidence country with over 50% of TB cases in the foreign-born population primarily due to the high numbers of migrants entering the country via land or sea. As a case study to evaluate the value of screening in newly arrived migrants, the EDETECT-TB project in Italy implemented and evaluated active TB screening in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Four studies from the United Kingdom (UK) involved foreign-born immigrants, contacts of PTB index cases, people with substance use disorder, people experiencing homelessness, people with lower incomes and PLHIV as a target population [ 15 - 18 ]. Additionally, studies from Italy and Germany involved migrants, while the Belgian study focused on migrants as well as on asylum seekers, people in prison, contacts and other people who did not belong to any specific group [ 21 - 23 ]. Eight of the nine studies demonstrated that screening was cost-effective compared with no screening, the passive screening method or other alternatives [ 15 - 18 , 20 - 23 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Four studies from the United Kingdom (UK) involved foreign-born immigrants, contacts of PTB index cases, people with substance use disorder, people experiencing homelessness, people with lower incomes and PLHIV as a target population [ 15 - 18 ]. Additionally, studies from Italy and Germany involved migrants, while the Belgian study focused on migrants as well as on asylum seekers, people in prison, contacts and other people who did not belong to any specific group [ 21 - 23 ]. Eight of the nine studies demonstrated that screening was cost-effective compared with no screening, the passive screening method or other alternatives [ 15 - 18 , 20 - 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, studies from Italy and Germany involved migrants, while the Belgian study focused on migrants as well as on asylum seekers, people in prison, contacts and other people who did not belong to any specific group [ 21 - 23 ]. Eight of the nine studies demonstrated that screening was cost-effective compared with no screening, the passive screening method or other alternatives [ 15 - 18 , 20 - 23 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Over 50% of TB cases in Italy are foreign born migrants. Goscé et al (2021) describe the EDETECT-TB project in Italy which implemented and evaluated active TB screening in the migrant population and their study confirmed that early case detection is a cost-effective intervention and that targeted post-arrival early screening ensures that potential further transmission is averted.…”
mentioning
confidence: 86%